The Use of Puppets in Teaching Speaking for Junior High School Students - Prasetyaningrum, Ari (Universitas Hamzanwadi, 2017)
This purpose of this research is to find the effectiveness of teaching speaking by using puppet for the junior high school students and how effective the use of puppet in teaching speaking for the junior high school students. The method applied in the present research was pre-experimental with one group pre test and post test design. The population of the test was 28 and all the students were the sample as well. To collect the data, a pre test and post test were administered with oral test as the instrument. The results of pre test and post test were used to determine the mean score and standard deviation score. In analyzing the data, a paired sample t-test was used to analyze whether the alternative was accepted of rejected. To analyze the data, the present researcher applied SPSS 17 for windows. Based on the result of data analysis, the mean score of pre-test was 50.00 and that of post test was 68. 75, meaning that there was a difference in the mean scores between the pre test and post test. In tetsing hypothesis, the present researcher found that t (df=27) = -7.232 at p= 0. 000, meaning hat the alternative hypothesis was accepted. It was concluded that puppet usage was significantly effective in teaching speaking for the junior high school students.